KAJIAN INSENTIF PENGOLAHAN KAKAO FERMENTASI UNTUK PETANI DAN KELOMPOK TANI - Satriawan, I Ketut (Universitas Udayana, 2007)
Cocoa is a prospective commodity export and as a superior commodity of estate crops in Bali. The quality of cocoa is very various and majority farmer processing it without fermentation.This research aimed to determine minimal price of raw material of wet bean cocoa from the farmer and difference price between fermented and non-fermented cocoa as processing incentive which must be give to the farmer. The research was done in the farmer group of estate crops of Tabanan Regency.The processing unit of the farmer group of estate crops must be buy a wet of cocoa bean from the farmer is with minimal price Rp. 4.180 per kg. Difference price fermented and non-fermented cocoa as processing incentive which must be give to the farmer is minimal Rp. 4.590 per kg, if the price of non-fermented cocoa is Rp. 11.000 per kg.